Some guidelines for determining foot-and-mouth disease vaccine strain matching by serology - Mattion, Nora Marta (2009)
The selection of matching strains for use in outbreaks of foot-and-mouth disease (FMD) virus can be assessed in vivo or by serological r-value determination. Sera from animals involved in vaccine potency and cross-protection trials performed using the "Protection against Podal Generalization" (PPG) test for two serotype A strains were collected and analyzed by the virus neutralization test (VNT) and liquid-phase ELISA (lpELISA) in three laboratories. The average VNT r-values for medium and high serum titer classes from the A24 Cruzeiro vaccinated animals were in line with the A/Arg/01 heterologous PPG outcome for all testing laboratories, suggesting that the vaccine strain A24 Cruzeiro is unlikely to protect against the field isolate A/Arg/01. The corresponding lpELISA r-values were slightly higher and indicate a closer relationship between both strains. Pooling of serum samples significantly reduced the inter-animal and inter-trial variation. The results suggest that a suitable reference serum for vaccine matching r-value experiments might be a pool or a medium to high VNT or lpELISA titer serum. Furthermore, the VNT seems to produce the most reproducible inter-laboratory results. More work is, however, needed in order to substantiate these claims.